Even a Little Bit Helps: An Implementation and Experimental Evaluation of Cognitive-Behavioral Therapy for High-Risk Probationers - Barnes, Geoffrey Carroll (Criminal justice and behavior, 2017)
Cognitive-behavioral therapy (CBT) is one of the most promising and widely used therapeutic approaches to reducing recidivism among criminal populations. Although many studies have evaluated CBT for this express purpose, few have done so in a community correctional environment. This article reports findings from a randomized field trial evaluating, “Choosing to Think, Thinking to Choose,” a CBT program designed specifically for a community correctional setting, and its impact on the recidivism of high-risk offenders. High-risk probationers were assigned to either standard, intensive probation (n = 447) or to the treatment condition (n = 457), where they received the same supervision intensity while also being directed to a classroom-based, 14-week CBT program. Twelve months after random assignment, intention-to-treat (ITT) analyses indicate that the overall CBT group was significantly less likely to reoffend, although this effect is concentrated in measures of nonviolent offending.